A neuropeptide signaling pathway regulates synaptic growth in Drosophila. - Chen, X.; Ganetzky, B. (Journal of Cell Biology, 2012)
Neuropeptide signaling is integral to many aspects of neural communication, particularly modulation of membrane excitability and synaptic transmission. However, neuropeptides have not been clearly implicated in synaptic growth and development. Here, we demonstrate that cholecystokinin-like receptor (CCKLR) and drosulfakinin (DSK), its predicted ligand, are strong positive growth regulators of the Drosophila melanogaster larval neuromuscular junction (NMJ). Mutations of CCKLR or dsk produced severe NMJ undergrowth, whereas overexpression of CCKLR caused overgrowth. Presynaptic expression of CCKLR was necessary and sufficient for regulating NMJ growth. CCKLR and dsk mutants also reduced synaptic function in parallel with decreased NMJ size. Analysis of double mutants revealed that DSK/CCKLR regulation of NMJ growth occurs through the cyclic adenosine monophosphate (cAMP)-protein kinase A (PKA)-cAMP response element binding protein (CREB) pathway. Our results demonstrate a novel role for neuropeptide signaling in synaptic development. Moreover, because the cAMP-PKA-CREB pathway is required for structural synaptic plasticity in learning and memory, DSK/CCKLR signaling may also contribute to these mechanisms.